Creativity and Innovation to Improve Processes in a Textile Industry - Alves, Caique; Felix Silva De Sousa, Joao Henrique (International Journal of Engineering and Management Sciences, 2021)
In this scientific work, the My Creative Idea (MIC) program was created and developed in the Coteminas S.A. textile industry, distributed among the organization's units in the country with emphasis on the São Gonçalo do Amarante unit in the state of Rio Grande do Norte. The aim was to critically analyze the improvements of industrial-scale processes resulting from the creativity and innovation intrinsically incorporated and experienced daily in the program. Thus, the general objective of the work was to evaluate the improvements in the productive processes coming from an innovation program in a textile industry, considering as specific propositions with respect to calculating the gains with reduction of losses, cost of implementation of ideas and measure financial returns and evaluate employee satisfaction according to the program. Moreover, there was free access in the company to be able to collect valuable information that could formalize a robust database for later structuring of the document, as well as the application of action research in the form of questionnaires. Therefore, the results verified clarified and emphasized the program's aggregating character to the organization in a general way under aspects that approach the financial spheres, the quality, and the satisfaction and motivation of the employees involved in this whole scenario. I suggest continuing to work on a continuous improvement methodology to further enhance My Creative Idea over the years, as well as insert this method of work to units that have not incorporated this program into their business strategies.